UR_GERICHTE 2015_OG S 15 vom 19. August 2015 - UR Obergericht (2015)
9. Strafprozessordnung. Art. 135 Abs. 1, Art. 135 Abs. 2, Art. 135 Abs. 3 lit. b, Art. 437 StPO. Art. 26 Gerichtsgebührenverordnung.